KORELASI HASIL BELAJAR MAHASISWA PADA MATA KULIAH ANATOMI TUMBUHAN DENGANMORFOLOGI TUMBUHAN DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UR - Nirullisa, Nirullisa; Fauziah, Yuslim; Syafii, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the correlation of student learning outcomes in subjects with Morphology Plant Anatomy Plant Biology at the Faculty of Teacher Education Program UR. This study is a descriptive correlational study. The population in the study were all students of Biology Faculty of Teacher Education Program UR. The study sample was student class of 2010 who have completed the course Plant Anatomy and Morphology of Plants by the number of 49 students. Sampling using purposive sampling, which is based on the consideration that the selected sample had completed college courses Plant Anatomy and Morphology of Plants that can provide in formation for the purpose of research. Data collection techniques a resecondary data from documents existing value in Biology Education Program and a closed primary data through questionnaires. Secondary data analysis technique performed through Product Moment Correlation test to identify student learning outcomes through value assignment, the value of UTS, the value of UAS and the final valueis obtained. While the student perceptions questionnaire analysis techniques to the implementation of the course Plant Anatomy and Morphology of Plants analyzed descriptively percentage with reference to the perception measurement scale Likert scale. The result sof research on the subject of Plant Anatomy Plant Morphology significant at 5% level with a correlation coefficient value assignment (0.90) a strong category, the value of UTS (0.61) medium category, the value of UAS (0.81) and the strong category final value (0.85) a strong category. This means there is a positive and significant correlation between student learning outcomes in subjects with Morphology Plant Anatomy Plant Biology at the Faculty of Teacher Education Program UR.Keywords: Correlation, Learning Outcomes, PlantAnatomy, Morphology ofPlants